CDC's guideline on pediatric mild traumatic brain injury: Recommendations for neurologists. Issue 3 (June 2019) - Weissman, Barbara; Joseph, Madeline; Gronseth, Gary; Sarmiento, Kelly; Giza, Christopher C.
Abstract : Purpose of review: In September 2018, the Centers for Disease Control and Prevention (CDC) published an evidence-based guideline on the diagnosis and management of mild traumatic brain injury (mTBI) among children. Recent findings: Based on a systematic review of the evidence that covers research published over a 25-year span (1990–2015), the CDC Pediatric mTBI Guideline strives to optimize the care of pediatric patients with mTBI. The guideline was developed using a rigorous methodology developed by the American Academy of Neurology. Summary: Clinical practice recommendations in the CDC Pediatric mTBI Guideline can help guide neurologists with critical diagnostic and management decisions and to implement evidence-based strategies for the recovery of their young patients with this injury.